Understanding Group Dynamics and Typology of Youth Travelers: A Comprehensive Study on Travel Preferences and Roles at Destination - Kusumah, Ahmad Hudaiby Galih (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThis research explores the group dynamics and typology of young travelers, classifying them into four distinct types: Leaders, Followers, Clowns, and Loners. Leaders assume responsibility for group decision-making and itinerary management, often prioritizing group comfort over personal enjoyment. Followers comply with group decisions and adapt their preferences to align with collective choices. Clowns, serving as group entertainers, contribute to a positive atmosphere, while Loners prefer solitude, engaging in personal activities even within the group context. The research highlights the concept of a